Medical Missionaries and Colonial Knowledge in West Africa and Europe, 1885-1914 Purity, Health and Cleanliness - Ratschiller Nasim, Linda Maria (Cambridge Imperial and Post-Colonial Studies, 2023)
This open access book offers an entangled history of hygiene by showing how knowledge of purity, health and cleanliness was shaped by evangelical medical missionaries and their encounters with people in West Africa. By tracing the interactions and negotiations of six Basel Mission doctors, who practised on the Gold Coast and in Cameroon from 1885 to 1914, the author demonstrates how notions of religious purity, scientific health and colonial cleanliness came together in the making of hygiene during the age of High Imperialism. The heyday of evangelical medical missions abroad coincided with the emergence of tropical medicine as a scientific discipline during what became known as the Scramble for Africa. This book reveals that these projects were intertwined and that hygiene played an important role in all three of them. While most historians have examined modern hygiene as a European, bourgeois and scientific phenomenon, the author highlights both the colonial and the religious fabric of hygiene, which continues to shape our understanding of purity, health and cleanliness to this day.